2011
DOI: 10.1128/iai.01370-10
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori VacA Induces Programmed Necrosis in Gastric Epithelial Cells

Abstract: Helicobacter pylori is a Gram-negative bacterium that colonizes the human stomach and contributes to the development of peptic ulcer disease and gastric cancer. The secreted pore-forming toxin VacA is one of the major virulence factors of H. pylori. In the current study, we show that AZ-521 human gastric

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
75
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 78 publications
(136 reference statements)
3
75
0
Order By: Relevance
“…The pore and channel forming by the N-terminal p33 domain alone drives pleiotropic cellular activities of VacA; i.e. vacuolation, mitochondria damage, apoptosis (10,47), autophagy (28,29), and programmed necrosis (27), suggesting that VacA may be characterized as a pore-forming toxin (47). Another study has indicated that both p33 and p55 are required to form a functional channel in the inner mitochondria membrane and trigger apoptosis (49).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pore and channel forming by the N-terminal p33 domain alone drives pleiotropic cellular activities of VacA; i.e. vacuolation, mitochondria damage, apoptosis (10,47), autophagy (28,29), and programmed necrosis (27), suggesting that VacA may be characterized as a pore-forming toxin (47). Another study has indicated that both p33 and p55 are required to form a functional channel in the inner mitochondria membrane and trigger apoptosis (49).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, VacA-induced cell death may occur through a programmed necrosis pathway in a caspase-independent process in AZ-521 cells (27). Therefore, we examined whether VacA-induced cell death resulted from autophagy via an LRP1-dependent pathway.…”
Section: Lrp-1 But Not Rptps Mediates Cleavage Of Caspase-7 and Parmentioning
confidence: 99%
See 1 more Smart Citation
“…A current model proposes that VacA monomers interact with the plasma membrane and subsequently oligomerize, which allows the formation of VacA pores in cell membranes (9). VacA causes a wide range of alterations in human gastric cells (9), including the formation of large cytoplasmic vacuoles (11,40), permeabilization of the plasma membrane (65), reduction of mitochondrial transmembrane potential (19,24,26,74), mitochondrial cytochrome c release (19,24,26,74), mitochondrial fragmentation (35), activation of mitogen-activated protein kinases (49), induction of autophagy (67), and cell death (13,26,35,53). Most of these effects (but not all) are dependent on membrane channel formation by VacA (30,34,46,71).…”
mentioning
confidence: 99%
“…VacA behaves as a passive urea transporter and, thus, it increases the permeability of the epithelium to urea, which is broken into intermediate toxic products. The infection by CagA positive strains is associated with more serious epithelial lesions, acute or chronic severe inflammation, possibility of peptic ulceration, and risk of gastric cancer (14)(15)(16) .…”
Section: Introductionmentioning
confidence: 99%